HUBUNGAN ANTARA TINGKAT PENDIDIKAN DAN PERSEPSI DENGAN PERILAKU IBU RUMAH TANGGA DALAM PEMELIHARAAN KEBERSIHAN LINGKUNGAN - Yoni Hermawan (Bumi Lestari Journal of Environment)
Circles Conception behaviour needed to public, create recontruction circlesconception that continuity (sustainable). Circles pollution in fact many in domination byhuman with various causal factor. This research is to dig up that education level relationship and perception with housewife’s behavior inside circles cleanliness.The research uses description method and corelational with taking housewife’s sampelin cupids sub district of Tasikmalaya town. The crop research showed that is foundpositive’s relation between education level and preception with housewife’s behavior insidecleanliness environment.